Ārṭ, kulcar aur tārīk̲h̲ : Pushto adab, Pushtūn tārīk̲h̲ aur ārṭ ke ḥavāle se maẓāmīn kā majmūʻah - Yūsufzay, Nūr al-Amīn (Pishāvar : Dī Prinṭ Main Prinṭarz, 2012)
Articles on Pushtuns customs and traditions.
Includes bibliographical references (page 90).
In Urdu; some in Pushto.
Keywords: Pushtuns -- Civilization; Pushtuns -- Social life and customs; Pushtuns -- Folklore; Pushtuns; Pushtuns -- Social life and customs; Folklore